Enhancement of the microstructural and mechanical properties of dental zirconia through combined optimized colloidal processing and cold isostatic pressing. Issue 2 (1st February 2019) - Aboras, Mohamed; Muchtar, Andanastuti; Azhari, Che Husna; Yahaya, Norziha; Mah, Joelle C.W.
Abstract: Agglomerates in 3 mol% yttria-stabilized tetragonal zirconia polycrystalline (3Y-TZP) powders introduce detrimental heterogeneities that drastically degrade the mechanical properties of the sintered zirconia. This study aimed to investigate the effectiveness of optimized colloidal processing combined with cold isostatic pressing (CIP) in the production of high-density 3Y-TZP with enhanced microstructural and mechanical properties. First, 3Y-TZP suspensions were prepared through colloidal processing with polyethyleneimine (PEI) as a dispersant. After the addition of PEI, the pH of the suspension was adjusted to optimize colloidal stability, which was ascertained through zeta potential measurements. 3Y-TZP green bodies were consolidated through slip casting and allocated into two groups. One group was subjected to CIP, and the other was not. The density, phase structure, microstructure, hardness, and flexural strength of the as-sintered 3Y-TZP samples were then examined. The sample with the highest colloidal stability was obtained with the suspension pH of 2 and PEI addition of 0.4 wt%. The as-sintered 3Y-TZP structures produced without CIP provided a relative density of 93% with an undesired monoclinic phase content of 2.1%. By contrast, 3Y-TZP structures subjected to CIP exhibited a tetragonal phase content of 100% and better mechanical properties, higher density, and more homogeneous microstructures than structures that were not subjected to CIP. Given these results, the optimized colloidal process combined with CIP can be used to successfully produce highly dense and homogenous 3Y-TZP structures with enhanced mechanical properties.